Gazzâlî’ye Göre Akıl ve Dinî Bilgi Kaynağı Olarak Aklın Önemi / The Intelect and its Value as a Source of Religious Knowledge According to al-Ghazzali - Yıldız, Mustafa (Journal of History Culture and Art Research, 2015)
Gazzâlî’ye Göre Akıl ve Dinî Bilgi Kaynağı Olarak Aklın Önemi / The Intelect and its Value as a Source of Religious Knowledge According to al-Ghazzali Öz Bu makalede Gazzâlî'nin dinî bilgi kaynağı olarak akla ne ölçüde önem verdiği konusu ele alınmaktadır. Makalede, Gazzâlî’ye göre dinî bilginin elde edilmesinde kelamî akıl (garize) anlayışının yeterli olmadığı ileri sürülmüştür. Gazzâlî bu eksikliği gidermek için kelamcıların akıl anlayışına filozofların akıl anlayışını ve sufilerin kalp anlayışını eklemek suretiyle yeni bir akıl anlayışı geliştirmiştir. Makale, Gazzâlî’nin ortaya koymuş olduğu bu akıl anlayışını detaylı bir şekilde incelemektedir. Makalenin giriş bölümünde dinî bilginin kaynağı ile ilgili olarak kelamcıların, filozofların ve sufilerin görüşlerine yer verilmiştir. Makalenin gelişme bölümünde ise Gazzâlî’ye göre akıl ile bilgi arasındaki ilişki ele alınmıştır. Bu bölümde Gazzâlî’nin akıl kelimesine yüklediği farklı anlamlar, mülk ve melekût âlemlerini anlamada aklın rolü ve kalp, ruh, nefis gibi kavramlara yüklediği anlamlar incelenmiştir. Daha sonra bilginin elde edilme yöntemleri ve Gazzâlî’nin bu konudaki değerlendirmelerine yer verilmiştir. Sonuç bölümünde ise Gazzâlî’nin akıl konusundaki düşüncelerinin dinî bilgi ve iman ile nasıl ilişkilendirildiği tartışılmıştır. The Intelect and its Value as a Source of Religious Knowledge According to al-Ghazzali Abstract This paper deals with how much importance is given to intellect as a source of religious knowledge by al-Ghazzali. The paper suggests that according to al-Ghazzali ghariza, the term which denotes the theologians’ understanding of intellect, is insufficient to acquire religious knowledge. Accordingly, he proposed a new understanding of intellect to overcome this insufficiency by combining it with the rationale soul of philosophers and the Sufis’ understanding of heart. This paper examines this novel understanding of intellect as proposed by al-Ghazzali in detail. In the introduction section, the views of theologians, philosophers and sufis about intellect as a source of religious knowledge are presented. In the development section, relations between the intellect and knowledge are discussed with respect to al-Ghazzali. In this section, Ghazzali’s varying use of the term intellect, its role in the understanding of the world of dominion and the world of sovereignity, and what he means with such terms like heart, soul, and self are examined. Afterwards, the methods of knowledge acquisition and al-Ghazzali’s position in this respect are given. In the conclusion section, it is explored how al-Ghazzali’s opinions about intellect are connected with religious knowledge and faith.